Promosi Produk Komunitas di Kampung Peng_Angguran Kota Metro - Nur Syamsiyah; Arinta Rahma Sari; Dwi Setiawati; Lisa Cahya Indriani (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
This training aims to help MSME actors to take advantage of social media and marketplaces to be used as a digital-based marketing strategy that is easy to use. The location of the service is in Kampung Peng_angguran, Yosodadi Village, RT 27, 28, 29, and RW 11, East Metro District, Metro Lampung City. The service method used is training in creating interesting content on social media, namely on Facebook and Instagram and creating an account on the marketplace. The results obtained in this training are increasing understanding in using and utilizing social media and marketplaces for commercial activities, namely product marketing easily and quickly